The effect of wine tourism experiences on wine brands - Correia, Ricardo (2016)
Wine tourism takes on a clear hedonic dimension, being especially prone to the design of experiences. The characteristics of wine tourism make this product quite compatible with the rural areas and with an evident capacity of sustainable development. Most of the studies that characterize the wine tourism experiences have a clear focus on the demand side. This paper aims at obtaining a greater insight into the leverage of the wine brands through positive experiences associated with wine tourism. Sustained on the Grounded Theory, a deep analysis of the perception that the cellars/farms have about the effect of their touristic offer on their wine brands was carried out. While there is no use of concrete measures on the supply-side, we found that there is the conviction of a reciprocal leverage effect between wine tourism experiences and wine brands. Despite the exploratory nature of this paper we conclude that wine experiences and brand value and awareness reinforce which other in an interactive and dynamic way.